Can enantiomer ligands produce structurally distinct homochiral MOFs? - Dubey, Mrigendra; Kumar, Ashish; Dhavale, Vishal M.; Kurungot, Sreekumar; Pandey, Daya Shankar (CrystEngComm, 2015)
Here, we report a self-assembled homochiral metal-organic framework [Cu-1.5(H2LL-leu)(Ac)H2O](n)center dot 3H(2)O (1) obtained from an L-leucine-derived ligand (H4L(L-leu)) and Cu(Ac)(2)center dot H2O in a 1 : 1 ratio. Coordination-induced conformational change in the ligand has been monitored by circular dichroism which has been further attested by synthesizing a D-leucine-containing enantiomer H4L D-leu and its Cu(II) complex [Cu-1.5(H2LD-leu)H2O](n)center dot 10H(2)O (2). Structure determination revealed entirely different structures for the homochiral MOFs (1 and 2) obtained from the L/D-leucine-derived enantiomer ligands under analogous reaction conditions. Further, structural dissimilarity in these MOFs has been judicially supported by proton conductance studies. MOF 1 shows higher proton (10(-5) S cm(-1)) conductance in comparison to 2 (10(-6) S cm(-1)) due to dissimilar alignment of the hydrogen-bonded water molecules in the hydrophilic pocket as well as crystal packing.

Cu-Pt nanocage with 3-D electrocatalytic surface as an efficient oxygen reduction electrocatalyst for a primary Zn-air battery - Dhavale, Vishal M.; Kurungot, Sreekumar (ACS Catalysis, 2015)
Cu-Pt nanocage (CuPt-NC) intermetallic structures have been prepared by an in situ galvanic displacement reaction. The structures are found to be well organized within the framework demarcated with distinguishing arms, having clear edges and corners with a size of similar to 20 nm. The unique nanocage structure possessing large specific surface area and better structural integrity helps to achieve improved electrochemical oxygen reduction reaction activity and stability in alkaline solution in comparison to the commercially available 20 wt % Pt/C. CuPt-NC shows 50 mV positive onset potential shift with significantly higher limiting current in comparison to Pt/C. Interestingly, CuPt-NC has shown 2.9- and 2.5-fold improved mass activity and specific activity, respectively, for ORR at 0.9 V vs RHE in comparison to Pt/C. Moreover, the stability of CuPt-NC has been tested by an accelerated durability test under alkaline conditions. CuPt-NC has been subsequently utilized as the air electrode in a primary Zn-air battery and is found to possess 1.30- and 1.34-fold improved power density and current density at 1 V, respectively, in comparison to the state-of-the-art Pt/C catalyst. In addition, CuPt-NC has shown several hours of constant discharge stability at 20 mA cm(-2) with a specific capacity of 560 mAh gZn(-1) and energy density of 728 Wh kgZn(-1) in the primary Zn-air battery system.
Keywords: 3-D electrocatalytic surface; Cu-Pt nanocage; electrocatalyst; galvanic displacement; oxygen reduction reaction; solvothermal method; Zn-air battery